Analisis Penggunaan E-Filing oleh Wajib Pajak Orang Pribadi dengan Menggunakan UTAUT 2 - Novia Triana Dewi, Ni Putu; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 30 No 12 (2020), 2020)
The purpose of this study is to  find out the factors affecting personal taxpayers to use e-Filing based on Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). This research conducted on individual taxpayers of e-filing users in 2018 registered at the Tabanan Primary Tax Service . The method used is non-probability sampling with accidental sampling technique. Data collected by distributing questionnaires to 100 individual taxpayers. The analysis technique used is multiple linear regression. Based on the results of the analysis that the performance expectations, sosial factor, facilitating condition and hedonic motivation have no effect on the use of e-Filing by individual taxpayers, effort expectation, price value and habit have a positive effect on the use of e-Filing by individual taxpayers in Tabanan Primary Tax Service. Keywords: E-Filing, Personal Taxpayers, UTAUT 2.